Changes in m6A RNA methylation of goat lung following PPRV infection - Raja Ishaq Nabi Khan; Manas Ranjan Praharaj; Waseem Akram Malla; Neelima Hosamani; Shikha Saxena; Bina Mishra; Kaushal Kishor Rajak; Muthuchelvan Dhanavelu; Ashok Kumar Tiwari; Basavaraj Sajjanar; Ravi Kumar Gandham; B.P. Mishra (Heliyon, 2023)
Peste des petits ruminants (PPR) is an acute, highly contagious viral disease of goats and sheep, caused by the Peste des petits ruminants virus (PPRV). Earlier studies suggest the involvement of diverse regulatory mechanisms in PPRV infection. Methylation at N6 of Adenosine called m6A is a type RNA modification that influences various physiological and pathological phenomena. As the lung tissue represents the primary target organ of PPRV, the present study explored the m6A changes and their functional significance in PPRV disease pathogenesis. m6A-seq analysis revealed 1289 m6A peaks to be significantly altered in PPRV infected lung in comparison to normal lung, out of which 975 m6A peaks were hypomethylated and 314 peaks were hypermethylated. Importantly, hypomethylated genes were enriched in Interleukin-4 and Interleukin-13 signaling and various processes associated with extracellular matrix organization. Further, of the 843 differentially m6A-containing cellular transcripts, 282 transcripts were also found to be differentially expressed. Functional analysis revealed that these 282 transcripts are significantly enriched in signaling by Interleukins, extracellular matrix organization, cytokine signaling in the immune system, signaling by receptor tyrosine kinases, and Toll-like Receptor Cascades. We also found m6A reader HNRNPC and the core component of methyltransferase complex METTL14 to be highly upregulated than the m6A readers – HNRNPA2B1 and YTHDF1 at the transcriptome level. These findings suggest that alteration in the m6A landscape following PPRV is implicated in diverse processes including Interleukin signaling.